Using physical principles in the segmentation of objects represented in images - Patrícia C. T. Gonçalves (2008)
Usually, image segmentation is the first high-level task to extract information from an image, which can constitute one of the first steps to build a solid model of an organ and other structures of the human body, for example. Region segmentation distinguishes different areas of an image, and contour segmentation delimits the different regions by their frontiers. The main goal of this work is to extract the contour of an object represented in an image after the definition of an initial contour for it. This contour, roughly defined by the user, will evolve along an iterative process until it reaches the border of the desired object. For that purpose, deformable models are used, whose behaviour is guide by physical principles. To determine that behaviour, the dynamic equilibrium equation, also known as equation of motion, is applied to an elastic physical model of the contour used in the segmentation process. The first step of the methodology used in this work consists in drawing on the input image a contour shape suitable for the object to segment, which is considered as the initial segmentation contour for that object. Next, this contour is modelled according to physical principles using the Finite Elements Method. To move the physical model step forward to the border of the object to segment, the dynamic equilibrium equation is resolved having as stop criterion the equilibrium between the internal and external forces involved. The internal forces applied on the finite element model are defined based on the physical characteristics of the virtual material adopted for the model and the choose level of interaction between its nodes; and the external forces are defined in terms of the image features that best describe the object to segment, like edges for instance. The desired contour segmentation is achieved when all forces applied on the physical model are in equilibrium.